Pelatihan Pembuatan Media Ajar Pintu Lestari Indonesia (PITARIA) sebagai Alat Peraga untuk Memperkenalkan Budaya Indonesia pada IGTKI-PGRI Kabupaten Tanggamus - Ardhy, Ferly; Salman Alfarisi Salimu; Fitra Endi Fernanda; Rahelia Hidayat; Dava Ikhsan Almasir (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: This activity aims to, (1) improve the abilities and skills of teachers who are members of Ikatan Guru Taman Kanak-Kanak – Persatuan Guru Republik Indonesia (IGTKI-PGRI) in Tanggamus Regency in creating and developing innovative teaching media, (2) introducing regional culture through more innovative learning media, (3) making the process of introducing culture more interesting and attractive for students Methodology: This community service program is carried out in the form of training to groups (IGTKI-PGRI) for Tanggamus Regency. Activities were carried out by: (1) socialization about innovative learning media conducted by Aisyah Pringsewu University Lecturers, (2) Training on Skills in making Pintu Lestari Indonesia (PITARIA) teaching media using makeshift materials to produce interesting learning media, (3) implementing the use of PITARIA teaching media in the classroom directly to see students’ interest in PITARIA teaching media. Result: This training results in an increased understanding of the use of creative and innovative teaching media, as well as improved teacher skills in making interesting and innovative learning media to make learning about culture easier for students to understand. Limitation: The program’s sustainability could be limited if there is no plan in place for ongoing support, training, or resource provision after the initial program period. Contributions: This community service program is able to provide results under its initial purpose, which is to help improve teachers’ skills in making teaching media and introducing regional culture.